Sieved para-orthogonal polynomials on the unit circle - Marcellan, F.; Ranga, A. Sri [UNESP] (Elsevier B.V., 2014)
Sieved orthogonal polynomials on the unit circle were introduced independently by Ismail and Li (1992) [15] and Marcellan and Sansigre (1991) [19]. We look at the para-orthogonal polynomials, chain sequences and quadrature formulas that follow from the kernel polynomials of sieved orthogonal polynomials on the unit circle. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Sieved orthogonal polynomials on the unit circle; Para-orthogonal polynomials; Chain sequences